The Role of Mucosal Immunity in the Pathogenesis of Necrotizing Enterocolitis - Hodzic, Zerina; Bolock, Alexa M.; Good, Misty (Frontiers in Pediatrics, 2017)
Necrotizing enterocolitis (NEC) is the most devastating gastrointestinal disease of prematurity. Although the precise cause is not well understood, the main risk factors thought to contribute to NEC include prematurity, formula feeding, and bacterial colonization. Recent evidence suggests NEC develops as a consequence of intestinal hyper-responsiveness to microbial ligands upon bacterial colonization in the preterm infant, initiating a cascade of aberrant signaling events and a robust pro-inflammatory mucosal immune response. We now have a greater understanding of important mechanisms of disease pathogenesis, such as the role of cytokines, immunoglobulins, and immune cells in NEC. In this review, we will provide an overview of the mucosal immunity of the intestine and the relationship between components of the mucosal immune system involved in the pathogenesis of NEC, while highlighting recent advances in the field that have promise as potential therapeutic targets. First, we will describe the cellular components of the intestinal epithelium and mucosal immune system and their relationship to NEC. We will then discuss the relationship between the gut microbiota and cell signaling that underpins disease pathogenesis. We will conclude our discussion by highlighting notable therapeutic advancements in NEC that target the intestinal mucosal immunity.